The art of deception: Mediated communication strategies in customs and excise fraud - Kristanto, Septian Dawang; Rahmanto, Andre Noevi; Satyawan, Ignatius Agung (Universitas Bunda Mulia, 2025)
Current technological developments also play a role in the birth of new crimes in the world, call it cybercrime. This study discusses cybercrime: fraud on behalf of Customs within the scope of persuasion communication and mediated communication from perpetrators to their victims and seen through the theory of Computer Mediated Communication (CMC) and Elaboration Likelihood Model, and also saw the campaign